Artikel : Evaluasi Kualitas dan Kuantitas Penggunaan Antibiotika Pada Pasien Rawat Inap Dengan Demam Tifoid di RSUD Tangerang Selatan - Winarni, Gandes; Saputri, Laras Tri; Utami, Anissa; Hidayatri, Nurul (STIKes Kharisma Persada, 2024)
Typhoid fever is an acute infectious disease of the digestive system caused by Salmonella Typhi bacteria. This disease is a global problem, particularly in developing countries. The purpose of this study was to determine the sociodemographics of patients, determine the use of antibiotics based on the type of antibiotic and the quality and quantity of antibiotic use in typhoid fever patients in South Tangerang City Hospital. Methods Observational research was retrospectively analyzed using Gyssens and ATC/DDD methods. The research data were obtained from the medical records of patients who met the inclusion criteria from January to December 2023. The results showed that out of a total of 124 antibiotic prescriptions, ceftriaxone was the most commonly used antibiotic for typhoid fever therapy. The quality of antibiotic use was 21 (12.57%) declared rational (category 0) while others were irrational category IIIA (12.57%), category IIIB (36.53%), category IIA (34.73%) and category IIB (3.59%). The quantity of antibiotic use is in the use of cefixime at 76.4 DDD/100 patient-days, ceftriaxone at 54.3 DDD/100 patient-days, thiamphenicol at 11.5 DDD/100 patient-days, amoxicillin at 2.8 DDD/100 patient-days and ciprofloxacin at 1.4 DDD/100 patient-days. Ampicillin was 0.6 DDD/100 patient-days, in line with WHO standards. The results of this study are expected to be a reference and recommendation for the hospital as an evaluation and improvement material to improve the rationality of antibiotic use, recommendations for the preparation of hospital formularies and drug procurement in the next period with consumption patterns